2009
DOI: 10.1111/j.1600-6143.2008.02456.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes Following De Novo CNI-Free Immunosuppression After Heart Transplantation: A Single-Center Experience

Abstract: Renal impairment at the time of heart transplantation complicates the choice of subsequent immunosuppressive therapy. Calcineurin (CNI)-free regimens utilizing proliferation signal inhibitors (PSI) may mitigate against nephrotoxicity in this group; however, their effectiveness remains unclear.We present our 7-year experience with de novo CNIfree, PSI-based immunosuppression after heart transplantation. Of the 152 patients transplanted between July 1999 and July 2006, de novo immunosuppression regimens were 49 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…In September 1999, sirolimus was approved by the FDA for use in renal transplant recipients. In cardiac transplant recipients, sirolimus has been used to stabilize or improve renal function in patients with calcineurin inhibitor induced nephropathy (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21) and to improve or attenuate the progression of CAV (22)(23)(24)(25)(26)(27).…”
mentioning
confidence: 99%
“…In September 1999, sirolimus was approved by the FDA for use in renal transplant recipients. In cardiac transplant recipients, sirolimus has been used to stabilize or improve renal function in patients with calcineurin inhibitor induced nephropathy (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21) and to improve or attenuate the progression of CAV (22)(23)(24)(25)(26)(27).…”
mentioning
confidence: 99%
“…Leet et al. (13) reported outcomes of de novo CNI‐free immunosuppression after Htx in adults, and Cr clearance was significantly lower in the study group. They also reported serious side effects including increased early rejection, infections and pleural effusions.…”
Section: Discussionmentioning
confidence: 93%
“…Other adult studies have reported a beneficial effect of SRL in delaying progression of TCAD (11, 12). Unfortunately, the use of SRL without adjunct CNIs in adult Htx recipients has been shown to lead to an increased incidence of early rejection and infection when compared to CNI‐based regimens and has not been reported in pediatric heart recipients for primary immunosuppression (13).…”
mentioning
confidence: 99%
“…Indeed, one recent report warned of high rates of rejection after patients were switched to a corticosteroid plus MMF protocol. 29 Another pilot study showed concerning outcomes with a de novo CNI-free protocol, 30 which cannot at present be recommended.…”
Section: Acute Kidney Injury After Hematopoietic Cell Transplantationmentioning
confidence: 99%